Discussion: Comments on the Article Titled as “Bitlis Air Pollution Emission Inventory and Estimation of Health Effects by Multiple Linear Regression” (Journal of Natural Hazards and Environment, January 2019, 5(1): 1-10) - Edip Avşar (Doğal Afetler ve Çevre Dergisi)
According to the article published in Journal of Natural Hazards and Environment, titled as “Bitlis Air Pollution Emission Inventory and Estimation of Health Effects by Multiple Linear Regression” (January 2019, 5(1): 1-10); mass discharges for the parameters of SOx, NOx, PM10 and CO were estimated by means of 2015 burned coal data in Bitlis. In addition, the number of patients admitted to hospitals for respiratory diseases in Bitlis between 2012 and 2015 were obtained. The patient numbers and the emission data were used to estimate the number of patients in 2015 and a high correlation was observed between the number of patients calculated and the number of patients obtained. There were very important errors in the study. The amount of coal taken into account and some of the calculated emission factors were inaccurate, thus, the emission inventory was completely wrong. In this case, the correlation value was completely random. In this discussion, the findings of the discussed article were evaluated so that the readers benefiting from discussed article can see these mistakes.